(untitled) (International Current Pharmaceutical Journal, 2012)
Seizures are more common in children than in any other age group, except the elderly. In fact, there are several kinds of seizures that affect only children. Sometimes children outgrow their seizures but many need to be treated for their seizures for their entire life. The main objectives of this study are to study the physician prescribing pattern in pediatric seizures and to educate the patient care taker about the disease and the use of drugs in order to control seizures and improve the quality of life. A non invasive prospective observational study was done with 86 pediatric patients from 01.11.2010 to 30.04.2011. Females were found to be more prone to seizures; prevalence of seizure was more in children aged 1-5 years old. Febrile seizures (46.5%) are the most commonly observed type of seizure in children followed by tonic clonic seizures (21%) and complex partial seizures (14%). The other types of seizures observed are simple partial seizures (7%), status epilepticus (2.3%) and others (9.3%). We observed that Clobazam is the most commonly prescribed drug for prophylaxis of febrile seizures. Phenytoin, Clobazam and Sodium valproate were commonly used drug in children. We infer that monotherapy for seizure is effective choice of treatment. DOI: http://dx.doi.org/10.3329/icpj.v1i10.11851 International Current Pharmaceutical Journal 2012, 1(10): 328-331